Balance y perspectivas de la cooperación universitaria al desarrollo en España - Hernández Tristán, Rafael (Revista Española de Desarrollo y Cooperación, 2023)
The main role of universities as development actors should be in the fields of research, training and technology transfer. The article analyze the situation of Development Research (I> D) in DAC countries and the prospects opened up for the sector in the III Plan for Development Cooperation 2009-2012. In addition, it identifies the objectives and activities that characterize the university development cooperation (CUD, by its Spanish acronym) and its main current challenges that require improved instruments adapted to their characteristics. Finally, with CUD´s growth and diversification, the article proposes a reflection on the adequacy of its efforts to more stringent criteria of relevance and effectiveness.